1999
DOI: 10.1007/bf02560503
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of HCV-RNA in the saliva cell fraction of patients with chronic hepatitis C but no Evidence of HCV transmission among sexual partners

Abstract: The aims of this study were to evaluate the prevalence of HCV-RNA in different fractions of saliva taken from patients with chronic hepatitis C, to establish whether virologic parameters or disease severity exert any influence on the detectability of HCV-RNA in saliva, and to evaluate the prevalence of HCV infection in partners of HCV-infected subjects with respect to the presence of HCV-RNA in saliva. Sera samples and different fractions of saliva (whole saliva, surnatant, and cell fraction) from 48 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
3
30
2
Order By: Relevance
“…Another question concerning the sexual transmission of HCV is the presence of the virus in secretions, saliva 20,21 , semen 8,59 and menstrual blood 78 . Some studies raise the issue and discuss the most probable pathway of infection, and whether it is from men to women or from women to men.…”
Section: Souto Et Al (1994)mentioning
confidence: 99%
“…Another question concerning the sexual transmission of HCV is the presence of the virus in secretions, saliva 20,21 , semen 8,59 and menstrual blood 78 . Some studies raise the issue and discuss the most probable pathway of infection, and whether it is from men to women or from women to men.…”
Section: Souto Et Al (1994)mentioning
confidence: 99%
“…The various studies that have compared viral load with the presence of HCV-RNA in the saliva have shown both positive [9,15,23,27] and negative correlations [10,28]. We did not evaluate this association.…”
Section: Discussionmentioning
confidence: 98%
“…Five out of 38 publications reported100% HCV-RNA detection in saliva samples from HCV-positive patients [16,17,25,29,38]; however, only a few cases or only patients with sialoadenitis were considered in these studies, which may represent a caveat. When reports with sample sizes larger than 30 HCV-positive patients were considered separately, the broad variability of frequencies was evident, ranging from 0 to 66% [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This variation in HCV-RNA detection frequencies in saliva samples may be due to the saliva sampling method used.…”
mentioning
confidence: 99%
“…However, HCV RNA has been measured in the saliva of infected individuals independent of mucosal lesions and periodontal disease (Liou et al 1992, Fabris et al 1999, Hermida et al 2002, Lins et al 2005. Additionally, HCV could enter the saliva via peripheral blood mononuclear cells (PBMCs) (Roy et al 1998, Fabris et al 1999, Maticic et al 2001; however, the presence of HCV RNA in PBMCs and saliva have not been closely correlated (Young et al 1993).…”
mentioning
confidence: 99%
“…However, HCV RNA has been measured in the saliva of infected individuals independent of mucosal lesions and periodontal disease (Liou et al 1992, Fabris et al 1999, Hermida et al 2002, Lins et al 2005. Additionally, HCV could enter the saliva via peripheral blood mononuclear cells (PBMCs) (Roy et al 1998, Fabris et al 1999, Maticic et al 2001; however, the presence of HCV RNA in PBMCs and saliva have not been closely correlated (Young et al 1993). The detection of HCV RNA in saliva and the existence of a correlation between the viral load in saliva and other compartments have been demonstrated in previous studies (Mariette et al 1995, Hermida et al 2002, Eirea et al 2005 In this work, a quantitative PCR assay was used to determine HCV viral load levels in the saliva and serum of patients.…”
mentioning
confidence: 99%